New Era: Mavacamten for Obstructive Hypertrophic Cardiomyopathy - Woodland, Ma’Lik; Al-Horani, Rami A. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2023)
Obstructive hypertrophic cardiomyopathy results from asymmetric septal hypertrophy, which eventually obstructs the outflow of the left ventricle. Obstructive hypertrophic cardiomyopathy is linked to mutations in genes that encode for sarcomere proteins, including actin, β-myosin heavy chain, titin, and troponin. The mutations lead to structural abnormalities in myocytes and myofibrils, causing conduction irregularities and abnormal force generation. Obstructive hypertrophic cardiomyopathy is a chronic disease that worsens over time, and patients become at higher risk of developing atrial fibrillation, heart failure, and stroke. Up until recently, there were no disease- specific medications for obstructive hypertrophic cardiomyopathy. Nevertheless, the US Food and Drug Administration approved mavacamten on April 28, 2022, for the treatment of symptomatic obstructive hypertrophic cardiomyopathy (New York Heart Association class II to III) in adults to improve functional capacity and symptoms. Its approval was based on data from EXPLORER- HCM and EXPLORER-LTE (NCT03723655). Mavacamten is a novel, first-in-class, orally active, allosteric inhibitor of cardiac myosin ATPase, which decreases the formation of actin- myosin cross-bridges, and thus, it reduces myocardial contractility, and it improves myocardial energetics. It represents a paradigm-shifting pharmacological treatment of obstructive hypertrophic cardiomyopathy. In this review, we describe its chemical and mechanistic aspects as well as its pharmacokinetics, adverse effects and warnings, potential drug-drug interactions, and contraindications.
Keywords: stenosis